Combating piracy, armed robbery against ships and maritime terrorism: a Malaysian perspective - Ahmad, Muhamad Hassan; Mohamed Nafees, Seeni; Ali Mohamed, Ashgar Ali; Ansari, Abdul Haseeb (Lexis Nexis Malaysian Sdn Bhd, 2018)
This article primarily intends to analyse Malaysian criminal laws regulating some of the aforesaid maritime offences and propose pragmatic recommendations for legal reforms in combating piracy, armed robbery against ships and maritime terrorism within and beyond Malaysian waters.